2012
DOI: 10.1007/s00464-012-2595-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in obesity-related comorbidities: is gastric bypass better than sleeve gastrectomy?

Abstract: Laparoscopic sleeve gastrectomy markedly improves most obesity-related comorbidities. Compared to LRYGB, LSG may have equal in reducing sleep apnea, hyperlipidemia, hypertension, diabetes, and musculoskeletal disease. LRYGB appears to be more effective at GERD resolution than LSG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 35 publications
2
39
0
2
Order By: Relevance
“…Zhang compared vertical sleeve gastroplasty with gastric bypass and concluded that both promoted a similar reduction in sleep apnea, hyperlipidemia, hypertension, diabetes and musculoskeletal diseases. However, gastric bypass showed better results in resolution of gastroesophageal reflux disease 19 . The decrease in appetite occurs because the resection of the fundus results in the reduction of the levels of ghrelin and hence the secretion of growth hormone (GH) 15,24 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 98%
“…Zhang compared vertical sleeve gastroplasty with gastric bypass and concluded that both promoted a similar reduction in sleep apnea, hyperlipidemia, hypertension, diabetes and musculoskeletal diseases. However, gastric bypass showed better results in resolution of gastroesophageal reflux disease 19 . The decrease in appetite occurs because the resection of the fundus results in the reduction of the levels of ghrelin and hence the secretion of growth hormone (GH) 15,24 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 98%
“…The SG is an increasingly popular bariatric procedure because of its relative ease (compared with RYGB), a short learning curve (between 28 and 50 operations) [23,24], a low complication rate (with a GL rate around 2% [1,25]), good long-term weight loss (i.e., an excess weight loss Z50% more than 5 yr after SG [24,26,27]), and its ability to effectively correct obesity-related co-morbidities [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, hyperlipidemia, and diabetes mellitus have been studied extensively in the post-bariatric surgery patient with promising outcomes, although usually limited to short-or mid-term results [2,[4][5][20][21][22][23][24][25]. A meta-analysis by Heneghan et al revealed absolute improvement in SBP from 139 mm Hg to 124 mm Hg, LDL from 118 mg/dL to 94 mg/dL, and HbA 1c from 7.5% to 6.0% at 34 months average follow-up [21].…”
Section: Discussionmentioning
confidence: 99%